Case Report: Orbital Myositis and Myasthenia Gravis as Symptoms of Immune Reconstitution Inflammatory Syndrome in a Patient With Human Immunodeficiency Virus Infection - Wang, Yanli; Zhao, Ning; Yang, Jun; Wen, Ying (Frontiers in Immunology, 2020)
We present a case of a 37-year-old man with HIV infection who had been on antiretroviral therapy for one year. He was admitted to our hospital with red and swollen eyes, acute onset progressive exophthalmos, and intermittent diplopia endured for 7 days. His symptoms, exam, and imaging led to a diagnosis of immune reconstitution inflammatory syndrome associated orbital myositis. His symptoms improved considerably after glucocorticoid therapy. Following a reduction in the oral prednisone dose, he re-presented with left ptosis, which rapidly progressed to bilateral ptosis. Diagnostic testing led to the diagnosis of immune mediated myasthenia gravis. Treatment with pyridostigmine bromide, prednisone, and tacrolimus was initiated. One month later, the patient’s symptoms improved significantly. There was a probable association between his symptoms and autoimmune immune reconstitution inflammatory syndrome. This report highlights the importance of recognizing autoimmune disorders in human immunodeficiency virus-infected patients undergoing antiretroviral therapy. Orbital myositis and myasthenia gravis in human immunodeficiency virus-infected patients correlate closely with immunity status following a marked increase in CD4+ T cell counts.